Guillain- Barre Syndrome: A Rare Immune Mediated Polyneuropathy - Keerthi, Nama Ravi Sneha; Meera, Neelathahalli Kasturirangan (Indian Journal of Pharmacy Practice)
Guillain-Barré Syndrome (GBS) is a rare autoimmune disorder associated with demyelinating polyneuropathy requiring early diagnosis and accurate treatment. From birth to 30 years, the annual incidence is fairly uniform at 1.3 to 1.9 per 100,000. Clinical hallmarks include symmetrical flaccid muscle paresis and areflexia in the presence of an increased cerebrospinal fluid protein and electrophysiologic studies demonstrating demyelination. A case of 29 year old female presenting to a tertiary care hospital with GB syndrome and hypothyroidism is described. The significance of an appropriate diagnosis by the physician and subsequent management by the clinical staff is reviewed.
Keywords: Autoimmune; Areflexia; Demyelination; Demyelinating polyneuropathy; Flaccid muscle paresis; Hypothyroidism